Pemberdayaan Guru Sekolah Dasar Negeri Arjosari Kabupaten Pacitan - Imam Kurdi (Jurnal VARIDIKA, 2015)
Elementary School Teacher Empowerment Arjosari Pacitan. Thesis. Surakarta, Muhammadiyah University of Surakarta, Graduate Program, 2013. To realize that schools have the advantage of the quality of education necessary for the management of the principal strategies in managing human resources. This study aims to describe the procurement teacher recruitment. Describe the formation and development of teachers, and describe the teacher control SDN Arjosari. This study is a qualitative, using an ethnographic approach. Place of execution of the research is on SDN Arjosari Pacitan. With sources: Head of School, teacher, chairman of the committee, and the school superintendent. The collection of data through observation, interviews and documentation. The validity of the data was tested by using triangulation. whereas for data analysis techniques using version Milles and Huberman. by means of data reduction, data and drawing conclusions and verification. The results showed that to meet the needs of teachers and kuantitati qualitatively as teacher empowerment has been done. (1) stats and implementation of teacher recruitment. (2) The development of (professionalism, career and welfare of teachers), and (3) control of teachers, good running order the expected goals.